2008
DOI: 10.1111/j.1467-7652.2008.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic tomato plants alter quorum sensing in plant growth‐promoting rhizobacteria

Abstract: Summary Two Gram‐negative, plant growth‐promoting rhizobacteria (PGPRs), denominated as M12 and M14, were classified by 16S rDNA sequencing as Burkholderia graminis species. Both strains were shown to produce a variety of N‐acyl‐homoserine lactone (AHL) quorum sensing (QS) signalling molecules. The involvement of these molecules in plant growth promotion and the induction of protection against salt stress was examined. AHL production was evaluated in vitro by thin‐layer chromatography using AHL biosensors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 54 publications
3
36
0
Order By: Relevance
“…It was established that the BraI/R XEN , BraI/R UNA , and BraI/ R KUR systems respond to C 14 -3-oxo-HSL. This is in accordance with previous studies which demonstrated that other members of the cluster, namely, B. phytofirmans (strains PsJN T and RG6-12) and B. graminis (strains M1 and M14), produce C 14 -3-oxo-HSL (7,77). In summary, these results suggest that 3-oxo-C 14 -HSL is the most probable cognate AHL for the BraI/R-like systems in this Burkholderia cluster.…”
Section: Discussionsupporting
confidence: 81%
“…It was established that the BraI/R XEN , BraI/R UNA , and BraI/ R KUR systems respond to C 14 -3-oxo-HSL. This is in accordance with previous studies which demonstrated that other members of the cluster, namely, B. phytofirmans (strains PsJN T and RG6-12) and B. graminis (strains M1 and M14), produce C 14 -3-oxo-HSL (7,77). In summary, these results suggest that 3-oxo-C 14 -HSL is the most probable cognate AHL for the BraI/R-like systems in this Burkholderia cluster.…”
Section: Discussionsupporting
confidence: 81%
“…Quorum sensing plays an important role in regulation of growth and function of various soil bacteria, including symbionts and some pathogens (including Pseudomonas spp.) that are known to inhabit the rhizosphere (Barriuso et al, 2008;Teplitski et al, 2011). However, research concerning how such factors might shape microbial communities and their functionality in processes like P mobilization are unknown.…”
Section: Ecological Considerations and Future Prospectsmentioning
confidence: 99%
“…When the QS molecule reaches a threshold concentration, microbes sense the extracellular signal, and the genes controlled by these mechanisms regulate their expression (7,8). This phenomenon was first studied in bacteria (9,10) and much later reported in fungi, particularly in the pathogenic yeast Candida albicans (11,12), where the sesquiterpene alcohol farnesol (1-hydroxy-3,7,11-trimethyl-2,6,10-dodecatriene) was described as the first QS molecule in eukaryotic organisms (11). However, over the years, other molecules, such as aromatic alcohols, tyrosol, dodecanol, ␥-butyrolactone, or ␥-heptalactone, have been identified as mediators of QS processes in these organisms (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%